2020
DOI: 10.1029/2018jb016463
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Lithosphere‐Asthenosphere Boundary

Abstract: Plate tectonic theory was developed 50 years ago and underpins most of our understanding of Earth's evolution. The theory explains observations of magnetic lineations on the seafloor, linear volcanic island chains, large transform fault systems, and deep earthquakes near deep sea trenches. These features occur through a system of moving plates at the surface of the Earth, which are the surface expression of mantle convection. The plate consists of the chemically distinct crust and some amount of rigid mantle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 338 publications
(650 reference statements)
8
70
0
Order By: Relevance
“…The first option is sugggestive of ponding beneath a permeability barrier, and therefore likely also includes migration and/or ephemeral character, and therefore we proceed discussing the latter two options. Similar observations of disconnected slow velocity anomalies have been observed in previous studies at more developed rifts or ridges, which hypothesise lateral melt migration is occuring along a permeability boundary (Braun & Sohn, 2003;Ghods & Arkani-Hamed, 2000;Harmon et al, 2020;Holtzman & Kendall, 2010;Rychert et al, 2020;Varga et al, 2008;Wang et al, 2020) and/or melt is ephemeral (Harmon et al, 2020;Rychert et al, 2020;Wang et al, 2020). Within the MER we also observe the slowest velocity anomalies at asthenospheric depths in our model, are not located directly beneath the slowest crustal velocity anomalies (Figure 9).…”
Section: Asthenospheric Anomaliessupporting
confidence: 91%
“…The first option is sugggestive of ponding beneath a permeability barrier, and therefore likely also includes migration and/or ephemeral character, and therefore we proceed discussing the latter two options. Similar observations of disconnected slow velocity anomalies have been observed in previous studies at more developed rifts or ridges, which hypothesise lateral melt migration is occuring along a permeability boundary (Braun & Sohn, 2003;Ghods & Arkani-Hamed, 2000;Harmon et al, 2020;Holtzman & Kendall, 2010;Rychert et al, 2020;Varga et al, 2008;Wang et al, 2020) and/or melt is ephemeral (Harmon et al, 2020;Rychert et al, 2020;Wang et al, 2020). Within the MER we also observe the slowest velocity anomalies at asthenospheric depths in our model, are not located directly beneath the slowest crustal velocity anomalies (Figure 9).…”
Section: Asthenospheric Anomaliessupporting
confidence: 91%
“…A weak decrease in the magnitude of anisotropy beneath seafloor >80 Myr from these studies is not observed in the few points in our compilation. However, lithospheric properties from regional studies typically exhibit more variability than trends gleaned from age averages of global models (Rychert et al., 2020). Comparisons between P wave anisotropy from refraction work in the western Atlantic suggested weak lithospheric anisotropy, interpreted as the result of slower spreading, for instance, in comparison to the Pacific (e.g., Gaherty et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the Pacific, a comparison with other body-wave techniques not affected by reverberations (e.g., SS precursors), indicates that our inferred seismic LAB depth is broadly consistent with early results (Gaherty et al, 1996;Ma et al, 2020;Tan & Helmberger, 2007) (see summary in Figure 12). Although the SS precursor technique seems to show an age dependence for normal Pacific lithosphere (C. Rychert et al, 2020;C. A. Rychert et al, 2018b), the very high resolution of our receiver function results (∼1.5 Hz) allows us to improve on the resolution of the inferred depth and sharpness of the seismic LAB.…”
Section: Discussionmentioning
confidence: 87%